Simultaneous determination of arginine, citrulline, and asymmetric dimethylarginine in plasma by reverse-phase high-performance liquid chromatography - Rao, P. V. L. N Srinivasa (J Lab Physicians, 2017)
BACKGROUND: Arginine, citrulline and asymmetric dimethylarginine (ADMA) are three molecules in the nitric oxide (NO) pathway which provide useful information about vascular endothelial function. ADMA accumulates with patients with chronic kidney disease (CKD) and inhibits NO synthesis. We describe the modification of a previously established method for the measurement of amino acids analysis for simultaneous detection of arginine, citrulline, and ADMA in plasma and to validate its performance in patients with CKD. MATERIALS AND METHODS: Arginine, citrulline, and ADMA were simultaneously separated by reverse-phase high-performance liquid chromatography by precolumn derivatization with O-phthalaldehyde using the modified method. It was then applied for analysis in thirty patients with CKD and thirty healthy controls so as to cover the entire measuring range, i.e., normal and uremic range. RESULTS: The method showed a good performance in terms of linearity, precision, and recovery. The detection limit of the assay for ADMA was found to be 0.05 μmol/L at a signal-to-noise ratio of 3:1. The average within run coefficient of variation for ADMA using this method was 4.7% in the normal range and 1.9% in the uremic range, while the average between-day precision in the normal and uremic range was 6.5% and 5.2%, respectively. Patients with CKD were found to have higher concentration of ADMA compared to controls. CONCLUSION: This method can be useful in assessing the baseline cardiovascular risk in an individual as well as in the follow-up of the patients who are receiving L-arginine, and thus, assess the response to treatment by simultaneous measurement of arginine and ADMA.